El análisis del impacto de la implementación de las normas internacionales de información financiera para PYMES del sector textil del Ecuador - Ortiz Carbo, Marie Francis (2019)
The present title work under the name of "The analysis of the impact of the implementation of International Financial Reporting Standards for SMEs in the textile sector of Ecuador" is responsible for analyzing the impact derived from the change of an accounting standard to a new one that It requires a lot of work and effort on the part of the people in the accounting department and those related to it. The companies with a greater number in Ecuador correspond to SMEs, being these entrepreneurial businesses of short trajectory with a view to grow in the long term, tend to have administrative and financial problems due to lack of investment in trained personnel working in the areas more vulnerable. The textile activity is developed throughout Ecuador, for this study the companies that are located within the city of Guayaquil are considered……….